Effective action for QED with fermion self-interaction in D=2 and D=3 dimensions - Abreu, EMC; Dalmazi, D.; Dutra, Alvaro de Souza [UNESP]; Hott, M. (American Physical Soc, 2002)
In this work we discuss the effect of the quartic fermion self-interaction of Thirring type in QED in D=2 and D=3 dimensions. This is done through the computation of the effective action up to quadratic terms in the photon field. We analyze the corresponding nonlocal photon propagators nonperturbatively in k/m, where k is the photon momentum and m the fermion mass. The poles of the propagators were determined numerically by using the MATHEMATICA software. In D=2 there is always a massless pole whereas for strong enough Thirring coupling a massive pole may appear. For D=3 there are three regions in parameter space. We may have one or two massive poles or even no pole at all. The interquark static potential is computed analytically in D=2. We notice that the Thirring interaction contributes with a screening term to the confining linear potential of massive two-dimensional QED (QED(2)). In D=3 the static potential must be calculated numerically. The screening nature of the massive QED(3) prevails at any distance, indicating that this is a universal feature of D=3 electromagnetic interaction. Our results become exact for an infinite number of fermion flavors.